Differences in ichthyofauna composition among tropical seagrass habitats in the small semi-enclosed bay - HUSAIN LATUCONSINA; ILHAM ZULFAHMI; HAMDANI DWI PRASETYO; AHMAD MUHTADI RANGKUTI; MUHAMMAD NUR; NERI KAUTSARI; ILHAM MARASABESSY (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Latuconsina H, Zulfahmi I, Prasetyo HD, Rangkuti AM, Nur M, Kautsari N, Marasabessy I. 2025. Differences in ichthyofauna composition among tropical seagrass habitats in the small semi-enclosed bay. Biodiversitas 26: 992-1007. The seagrass ecosystem is an important habitat for ichthyofauna in coastal waters and small islands in tropical areas. The richness of ichthyofauna species in seagrass habitats is highly dependent on the physical characteristics of the habitat and the support of other nearby habitats. This research aims to compare the number of species, families and orders of ichthyofauna among different seagrass habitats in the waters of a semi-enclosed bay. The research stations were based on different seagrass habitats in Inner Ambon Bay (IAB), Maluku, Indonesia, single-vegetation seagrass meadows and mixed-vegetation seagrass meadows. We conducted fish sampling using beach seines at monthly intervals for one year. We collected a total of 10,772 fish specimens representing 123 species from 46 families and 22 orders. Of note, 69.1% were juveniles. Different species were present in different seagrass habitats, each with its own physical characteristics. Fish abundance, species richness, and similarity indices were higher in mixed-vegetation seagrass habitats than single vegetation habitats. Proximity between seagrass habitats supports high similarity in species, families and orders. Therefore, protecting different types of seagrass habitats is the right strategy for supporting the abundance and diversity of the ichthyofauna. In addition, the protection of habitats surrounding seagrass meadows, such as mangroves and coral reefs, which are ecologically linked through tidal migration of ichthyofauna, is also important to support the conservation of ichthyofauna to achieve sustainable fisheries use in IAB to support food security.